HUBUNGAN PERISTIWA ISRAK MIKRAJ DENGAN TEOR RELATIVITAS EINSTEIN - Hilda, Lelya (IAIN PADANGSIDIMPUAN, 2014)
Albert Einstein was a German-born theoretical physicist who developed the theory of relativity. The theory of relativity was representative of more than a single new physical theory. There are some explanations for this. First, special relativity was published in 1905, and the final form of general relativity was published in 1916. The theory of relativity has proved the truth of the events Israk Mikraj ascension. Israk Mikraj is not a metaphysical event. He is a physical event (real; physical) experienced and lived the Prophet Muhammad with his consciousness. The event of Israk and Mikraj are referred to briefly in the Qur'an. Within the Qur'an itself, there are two verses in chapter 17, which has been named after the Isra, and is called Surah Al-Isra. There is also some information in Surah An-Najm, which some scholars say is related to the Israk and Mikraj